Pengembangan Modul Online Berbasis Inquiry dengan Muatan Kearifan Lokal Sukabumi pada Materi Perubahan dan Pelestarian Lingkungan Hidup - Putri Nida Nurulaini; Setiono Setiono; Gina Nuranti (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2022)
This study aims to develop an inquiry-based online module with the content of Sukabumi local wisdom. This type of research is the development of the ADDIE development model (Analysis, Design, Development, Implementation, evaluation). The research subjects were biology teachers, 99 students of class X MIPA and social studies at SMA Negeri 1 Sukaraja and validators. The instruments used in this study were material expert validation sheets and media experts to obtain the results of the online module validity test and student response questionnaires with the teacher to obtain the online module practicality test results. The results of the study show that (1) Expert validation states that the online module is a very valid category in terms of material, learning and display aspects. (2) Teachers and students gave a very good response to the online module and included in the very practical category. Based on the results and discussion of the research, it can be concluded that the development of online modules using the ADDIE model with a validation and evaluation process at each stage can produce valid products and produce modules that have a high practical value.